1977
DOI: 10.1007/bf00428592
|View full text |Cite
|
Sign up to set email alerts
|

The salt relations of Dunaliella

Abstract: Dunaliella tertiolecta (marine) and D. viridis (halophilic) were each trained by serial transfer to grow at salt concentrations previously regarded as the other's domain. D. viridis then had a salt optimum at 1.0-1.5 M sodium chloride whereas that for D. tertiolecta was less than 0-2 M. Nevertheless D. tertiolecta grew faster than the halophil at all salt concentrations up to 3.5 M, the highest at which they were compared. Both species accumulate glycerol, which is necessary for growth at elevated salinities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This result could indicate a higher presence of the algae Dunaliella or a higher primary production of glycerol, which is the predominant compatible solute in Dunaliella or alternatively, the oxidation of glycerol to dihydroxyacetone, that has been studied in the species Salinibacter ruber and is used as a growth substrate by H. walsbyi and Haloferax volcanii (Elevi Bardavid and Oren, 2008; Ouellette et al, 2013). Therefore, glycerol and probably dihydroxyacetone are considered as the main carbon source and energy for the heterotrophic community in salterns (Borowitzka and Brown, 1974; Borowitzka et al, 1977; Ouellette et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…This result could indicate a higher presence of the algae Dunaliella or a higher primary production of glycerol, which is the predominant compatible solute in Dunaliella or alternatively, the oxidation of glycerol to dihydroxyacetone, that has been studied in the species Salinibacter ruber and is used as a growth substrate by H. walsbyi and Haloferax volcanii (Elevi Bardavid and Oren, 2008; Ouellette et al, 2013). Therefore, glycerol and probably dihydroxyacetone are considered as the main carbon source and energy for the heterotrophic community in salterns (Borowitzka and Brown, 1974; Borowitzka et al, 1977; Ouellette et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of glycerol, which has been called a 'compatible solute' by Brown & Simpson (1972), appears to be closely regulated by the external water activity rather than by a specific solute effect, since increased concentrations of organic substances, such as sucrose, sorbitol and 2-deoxy-D-glucose, in the external medium also trigger glycerol accumulation (Borowitzka et al, 1977). The alga initially responds to increasing water activity by swelling to about 30,um in diameter and then by dissimilating glycerol until the cell regains its usual size and shape.…”
mentioning
confidence: 99%
“…The cell may not withstand constant exposure to high salinity, which may relate to drain of ATP in the starch to glycerol conversion (Kaplan et al, 1980). Previous research has shown that D. viridis grows optimally in 1.0 -1.5 M NaCl and tolerates up to 4.0 M NaCl whereas D. salina grows best in 2.0 M NaCl and tolerates up to 6.0 M NaCl (Borowitzka et al, 1977). However D. viridis has been reported to grow optimally at 5.8 M NaCl and temperature of 30 o C (Jimenez and Niell, 1991).…”
Section: Resultsmentioning
confidence: 99%